Aesthetic of carnivalesque: Johannisnacht by Uwe Timm and Lietuvis Vilniuje by Herkus Kunčius - Katinienė, Violeta (Literatūra, 2019)
Carnivalisation in literary prose has been gaining prominence both in Lithuanian and German literature. The present paper compares two novels, namely, Johannisnacht by Uwe Timm (1996) and Lietuvis Vilniuje by Herkus Kunčius (2011), related not merely through their themes of current affairs and reflections of the past, but also through poetics which continues the tradition of Carnivalesque. Although the two authors represent distinctly different cultural and literary backgrounds of two countries (West Germany and Lithuania), the novels transcend to a common intercultural space by their similar narrative strategies and carnivalised worldview.
Keywords: contemporary German and Lithuanian novels; carnivalesque; comparative literature